Antibiotic resistance pattern of Methicillin-resistant Staphylococcus aureus in asymptomatic prisoners of Kathmandu valley - Shrestha, Sabin; Paudel, Asmita; Paudel, Saroj; Shakya, Manju Shree (Tribhuvan University Journal of Microbiology, 2022)
bjectives: The purpose of this study was to determine the prevalence of methicillin-resistant Staphylococcus aureus and its antimicrobial resistance among the prisoners within the prisons of Kathmandu valley. Methods: A total of 320 nasal samples were collected from the prisoners. S. aureus was confirmed by using standard microbiological techniques including culture and biochemical tests. MRSA was confirmed using cefoxitin disc and antimicrobial susceptibility testing was performed by Kirby-Bauer disc diffusion method results were interpreted according to the guidelines of Clinical Laboratory Standard Institute (CLSI). Results: Out of 320 samples, 41 (12.82%) isolates were confirmed S. aureus and 8 (19.51%) of them were screened as MRSA positive. Highest percentage of MRSA was found in the samples collected from Nakhu prison 6 (75%) followed by Central prison 1 (12.5%) and Juvenile Correctional Home 1 (12.5%). Majority of the of MRSA isolates (62.5%) were also found to be multiple drug-resistant strains. All of the MRSA (100%) were sensitive towards linezolid and resistant towards ciprofloxacin. Conclusion: The presence of methicillin-resistant S. aureus among the prisoners indicates the emergence of drug resistance in a vulnerable population which may lead to hazardous disease breakouts in the prison and even in the community after their release. Regular monitoring and its minimization should be done in order to control its dissemination.